2009
DOI: 10.1590/s1516-35982009000900019
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do sexo, do grupo racial e da idade ao abate nas características de carcaça e maciez da carne de caprinos

Abstract: RESUMO -Este trabalho foi realizado com os objetivos de quantificar e qualificar a carcaça e os cortes cárneos de cabritos de dois sexos (machos e fêmeas) e três grupos raciais -Alpino; ½ Boer + ½ Alpino (½ BA); e ¾ Boer + ¼ Alpino (¾ BA) -abatidos em três idades (aos 60, 90 e 120 dias de confinamento), visando avaliar o aproveitamento de cabritos provenientes de rebanhos leiteiros. As carcaças foram avaliadas pelas características de peso, rendimento, conformação, gordura de cobertura, comprimento interno e e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
(34 reference statements)
3
5
0
7
Order By: Relevance
“…This result agreed with other studies in which Boer-sired Fj kids out of Spanish or Alpine dams did not differ from straightbred Spanish and Alpine kids for carcass cut weight proportions (Cameron et al, 2001;Menezes et al, 2009). Some variation in cut weight proportions by genotype was noted in evaluations of straightbred Boer and unimproved indigenous goats in southern Africa, but the variation was not consistent by cut across the studies and breed comparisons were confounded with management environments Tshabalala et al, 2003).…”
Section: Live Carcass and Primal Weightssupporting
confidence: 90%
See 1 more Smart Citation
“…This result agreed with other studies in which Boer-sired Fj kids out of Spanish or Alpine dams did not differ from straightbred Spanish and Alpine kids for carcass cut weight proportions (Cameron et al, 2001;Menezes et al, 2009). Some variation in cut weight proportions by genotype was noted in evaluations of straightbred Boer and unimproved indigenous goats in southern Africa, but the variation was not consistent by cut across the studies and breed comparisons were confounded with management environments Tshabalala et al, 2003).…”
Section: Live Carcass and Primal Weightssupporting
confidence: 90%
“…This lack of difference among sire breeds was an extension of the absence of a sire breed effect for kid BW at weaning . In studies where Boer-sired F^ kids were compared with straightbred kids from common unimproved dam genotypes (e.g., local, Spanish), Boer sires were found to increase BW at slaughter and carcass weight by some (Oman et al, 2000;Merlos-Brito et al, 2008), but not by others (Cameron et al, 2001;Menezes et al, 2009;Rodrigues et al, 2009). Using BW endpoints for slaughter, Dhanda et al (2003) reported that age at slaughter and carcass weight did not differ between Boer x feral Fi kids and straightbred feral kids.…”
Section: Live Carcass and Primal Weightsmentioning
confidence: 99%
“…Esses valores foram compatíveis com a literatura (Grande et al, 2003;Hashimoto et al, 2007;Carvalho Jr. et al, 2009) Os valores observados por outros autores (Hashimoto et al, 2007, Carvalho Jr. et al, 2009Menezes et al, 2009;Costa et al, 2010), entre 0,16 e 0,26 para ICC, foram semelhantes aos obtidos neste estudo. Para ICP, valores entre 0,36 e 0,40 foram observados, inferiores aos obtidos neste experimento, em que não foram observadas diferenças significativas para sistemas de terminação, nem para grupos genéticos (Tab.…”
Section: Resultsunclassified
“…Segundo Menezes et al (2009), os tecidos do lombo, músculo, gordura e osso tendem a aumentar com o avançar da idade do animal, acompanhando o crescimento e aumento de peso da carcaça; portanto, ao estudar esses componentes, pode-se extrapolar os resultados para a carcaça como um todo.…”
Section: Resultsunclassified
“…Essa morfometria também pode ser explicada pela idade avançada dos caprinos (20 meses), ou seja, os animais em maturidade. Corroborando com isso, Menezes et al (2009) …”
Section: Variávelunclassified